To solve the given system of equations, we have:
- \( x + 7y - z = 48 \) (Equation 1)
- \( y + 8z = 71 \) (Equation 2)
- \( z = 8 \) (Equation 3)
Let's substitute \( z = 8 \) (from Equation 3) into the other equations.
Substituting \( z = 8 \) into Equation 2:
\[ y + 8(8) = 71 \] \[ y + 64 = 71 \] \[ y = 71 - 64 \] \[ y = 7 \]
Now substituting \( y = 7 \) and \( z = 8 \) into Equation 1:
\[ x + 7(7) - 8 = 48 \] \[ x + 49 - 8 = 48 \] \[ x + 41 = 48 \] \[ x = 48 - 41 \] \[ x = 7 \]
We have found the values:
- \( x = 7 \)
- \( y = 7 \)
- \( z = 8 \)
Thus, the solution to the system of equations is:
Answer: A. The solution of the given system is \( x = 7 \), \( y = 7 \), and \( z = 8 \).